Laboratory Testing of Transovarial Transmission in Aedes Aegypti Mosquito - Guntur Benedict Hutadjulu; Sitti Rahmah Umniyati; Jarir At Thobari (Tropical Medicine Journal, 2012)
Introduction: Ae. aegypti is one of the vectors causing Dengue Hemorrhagic Fever (DHF) that feeds on human blood suffering from DHF and transmit it to another healthy human. The ability of Dengue Virus (DENV) to survive in nature is due to 2 mechanisms i.e. horizontal transmission among viremic vertebratae infected by Aedes mosquitos and vertical (transovarial) transmission from infected female mosquito to another generation.Objectives: To know the differences between next generation’s viral carriage, percentage ofmosquito descendants carrying DENV, and the distribution of DENV in its infected mosquitos.Methods: Study design was a quasi experimental posttest-only design with control group. The study was conducted on 53 second-generation female Ae. aegypti mosquitos which are grouped into treatment and control groups. Dengue Viral antigen in both groups were detected by immunohistochemistry method using Streptavidin Biotin Peroxidase Complex (SBPC) in paraffin embedding preparation of mosquitos aged 1-7 days. Fisher exact test was used to compare proportion of virus detected in moaquitos between 2 groups.Results: The virus detected in second generation of DEN-infected and uninfected mosquitos were 100% and 85.7%, respectively. The virus was distributed from day 1 to 7 in all organs such as brains, thorax, salivary gland, gastric epithelial cells, and ovarium of the infected mosquitos. Similar distribution was not detected in control mosquitoes.Conclusion: There was no difference in next mosquito generation’s transovarial infection among DENV-infected and uninfected Ae. aegypti mosquitos.Keywords: Ae. aegypti mosquito; Dengue virus (DENV); transovarial transmission; immunohistochemistry method, Streptavidin Biotin Peroxidase Complex (SBPC).